2010
DOI: 10.1111/j.1460-9592.2010.03457.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications in children with Apert syndrome: a review of 509 anesthetics

Abstract: We found there to be a low incidence of major perioperative major complications in this group of patients. Nevertheless, a significant proportion of these children have obstructive sleep apnoea and may develop supraglottic airway obstruction on induction and emergence from anesthesia due to the associated mid-face anatomical abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 14 publications
0
32
0
5
Order By: Relevance
“…In an emergency, an intraosseous or intramuscular route can be used. 2 These patients tend to sweat a lot and unlike other patients undergoing syndactyly surgery do not appear to need warming when undergoing peripheral surgery to their limbs. If they are actively warmed there is a risk of pyrexia, so temperature should always be monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an emergency, an intraosseous or intramuscular route can be used. 2 These patients tend to sweat a lot and unlike other patients undergoing syndactyly surgery do not appear to need warming when undergoing peripheral surgery to their limbs. If they are actively warmed there is a risk of pyrexia, so temperature should always be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…1 Children with Apert syndrome have a much higher incidence of perioperative airway and respiratory complications than other children. 1,2 We report our experience in the anaesthetic management of a case of Apert syndrome referred to us for endoscopy of upper respiratory tract and syndactyly release procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Even if intubation was easy, intraoperative respiratory complications are not uncommon. Case studies has reported increase in secretion and wheezing during anesthesia in Apert syndrome (4,(7)(8)(9). Increases in secretion may lead to desaturation and obstruction of tracheal tube (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of airway is a major concern for anesthesiologists in the patients with Apert syndrome (1,4). Ventilation by face mask may be difficult due to craniofacial malformations such as midface hypoplasia, choanal atresia and tracheal stenosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It is defined by the triad of syndactyly, craniofacial abnormalities, and craniosynostosis. Others conditions include developmental delay, bulging and downward-slanting eyes at the lateral canthus, cleft palate, abnormal occlusion, cervical vertebral fusion, and hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%